Microeukaryotic Community Shifting Along a Lentic-Lotic Continuum - Wang, Yixia; Ren, Ze; He, Ping; Xu, Jie; Li, Daikui; Liu, Cunqi; Liu, Bo; Wu, Naicheng (Frontiers in Ecology and Evolution, 2022)
As an important regulator of ecosystem functions in river systems, microeukaryotes play an important role in energy and material conversion, yet little is known about the shift along a lentic-lotic continuum. In this study, the 18S rRNA genes sequencing was used to identify the microeukaryotic communities at 82 sites along a lentic-lotic continuum with the aim of understanding the impact of upstream inlet river on microeukaryotic communities in Baiyang Lake (BYD) and its downstream. Our results showed that the upstream inlet river affected the diversity and community composition of microeukaryotes in BYD and downstream rivers, and environmental variables greatly affected the composition of microeukaryotic community. The community composition in BYD had lower variabilities. Co-occurrence network analysis revealed that the network was non-random and clearly parsed into 3 modules, and different modules were relatively more abundant to a particular area. As keystone taxa, some nodes of the upstream microeukaryotic network played an important role in structuring network and maintaining the stability of the ecosystem. In BYD and downstream, the microeukaryotic network was highly fragmented, and the loss of keystone taxa would have an adverse impact on the integrity and function of the microeukaryotic community. Microeukaryotes had strong tendencies to co-occur, which may contribute to the stability and resilience of microeukaryotic communities. Overall, these findings extend the current understanding of the diversity and community composition of microeukaryotic along a lentic-lotic continuum.